Analysis of Financial Ratio as an Indicator of Financial Performance - Windi; Fatmala, Wilda; Sari, Murni (International Journal of Multidisciplinary Learners, 2025)
The financial performance of a company can be known and measured using Financial ratio analysis is one of the instruments to analyze financial statements in a company. This study aims to determine the financial performance of PT Pos Indonesia by analyzing the ratio of liquidity, solvency, activity, and profitability. To assess the financial performance of PT Pos Indonesia, the purpose of this study is to find out the condition and performance based on financial ratios. The data used is secondary data. The type of research used is a type of quantitative descriptive research that aims to find factual information about the objects used in this study, namely financial statements in the form of balance sheets and income statements of PT Pos Indonesia for the period 2021 to 2023. The data analysis method used is a quantitative data analysis method. The results of the research from the liquidity ratio of the quick ratio position are said to be good while the current ratio and cash ratio are said to be poor. The solvency ratio of the debt to asset ratio is said to be unhealthy or unstable and the debt to equity ratio is said to be good. When viewed from the ratio of activities, the effectiveness level of PT Pos Indonesia is in poor condition because it is decreasing every year. The profitability ratio of NPM and ROE is said to be good while ROA is not in good condition.